2012
DOI: 10.1128/mcb.06175-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Liver X Receptor, Retinoid X Receptor, and Peroxisome Proliferator-Activated Receptor α in Mouse Liver Reveals Extensive Sharing of Binding Sites

Abstract: The liver X receptors (LXRs) are nuclear receptors that form permissive heterodimers with retinoid X receptor (RXR) and are important regulators of lipid metabolism in the liver. We have recently shown that RXR agonist-induced hypertriglyceridemia and hepatic steatosis in mice are dependent on LXRs and correlate with an LXR-dependent hepatic induction of lipogenic genes. To further investigate the roles of RXR and LXR in the regulation of hepatic gene expression, we have mapped the ligandregulated genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
236
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(267 citation statements)
references
References 95 publications
28
236
3
Order By: Relevance
“…Alternatively, C/EBP␣ and other cooperating factors are able to relax the sequence specificity so much that PPAR␥ can interact with nonconsensus sequences, e.g., direct repeat half sites. Consistent with this, previous work from our group indicated that both PPAR␣ and liver X receptor can associate directly with sequences that have relatively little resemblance to their consensus sequences (67).…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, C/EBP␣ and other cooperating factors are able to relax the sequence specificity so much that PPAR␥ can interact with nonconsensus sequences, e.g., direct repeat half sites. Consistent with this, previous work from our group indicated that both PPAR␣ and liver X receptor can associate directly with sequences that have relatively little resemblance to their consensus sequences (67).…”
Section: Discussionsupporting
confidence: 78%
“…Peaks were assigned to different genomic regions of associated target genes as described under "Results." RXR ChIP peak (33) and DNase hypersensitivity peak (available through the mouse ENCODE project) overlap were determined using custom scripts. For correlation of gene expression changes with differential peaks, we used the microarray data from Ad-TR␤1-PTU versus Ad-TR␤1-T3.…”
Section: Constructs and Generation Of Ad-blrp-tev-htr␤1mentioning
confidence: 99%
“…To evaluate whether the heterodimer is the predominant active form in vivo, we used data from a RXR ChIP-seq experiment from mouse liver that was previously done using an RXR␣ antibody (33). Importantly, the major heterodimer partner for TR in the liver is the RXR␣ isoform (34).…”
Section: Validation Of Binding Sites and Gene Expression Determined Bmentioning
confidence: 99%
“…ChIP Sequencing Analysis-Data analysis was performed using bowtie and HOMER (29) on previously published ChIP experiments: GSE50944 (30), GSE35262 (31), and GSE28319 (32). The sequencing experiment was normalized to a total of 10 7 uniquely mapped tags and visualized by preparing custom tracks for the UCSC Genome Browser.…”
Section: Plasmids and Expression Constructs-expressionmentioning
confidence: 99%